PENGUATAN PROTOKOL KESEHATAN DALAM UPAYA MENANGKAL COVID-19 KEPADA MASYARAKAT PESISIR SUAK INDRAPURI KABUPATEN ACEH BARAT - Mohamad Gazali; Dio Hidayat; M. Ali Sarong; Zuriat Zuriat; Hayatun Nufus; Rina Syafitri; Sulaiman Ali (Universitas Teuku Umar, 2021)
COVID-19 is a type of deadly virus that infects the human respiratory tract. Therefore, all activities must follow the health protocols follow published by the Indonesian Ministry of Health, such as social distancing, wearing masks and washing hands. The aim of this empowering community programme is to give the reinforcement for the Suak Indrapuri community that conducted routinity at coastal environment. In other hand, we also provided the touchless hand washer assistance to make it easier for people to do health protocols. This study which is a part of community service activity was conducted by using the lecture/mentoring method. The output of the activity is an increase of public awareness to always follow health protocols to every activity. The activity received a positive response from the local community. This can be seen from the enthusiasm of the community in participating in this community service activity.